Original paperEFFECTS OF BLOOD LACTATE ON OXYGEN UPTAKE KINETICS DURING RECOVERY AFTER SPRINT IN HUMANS - Yano, T.; Matsuura, R.; Arimistu, T.; Yamanaka, R.; Lian, C.; Afroundeh, R.; Kondou, S.; Yunoki, T. (Biology of Sport, 2012)
The purpose of this study was to examine the effects of blood lactate level (La) on oxygen uptake ( · VO2) kinetics during recovery after short-term exercise with maximal effort (sprint). Three sprints were performed on a cycle ergometer with a load of 8% of body weight at maximal rotation rate. · VO2 kinetics and oxygen debt were determined after three sprint tests: one 10-s cycling sprint, five repeated 10-s cycling sprints with 6-min intervals and one 30-s cycling sprint. There was no significant difference between peak power outputs in the 10-s sprint and five sprints. There was no difference in · VO2 kinetics during recovery from one sprint and during recovery after five sprints. La peaked at 5 min. The peak value of La was significantly lower in one sprint (4.41 ± 0.9 mM) than in five sprints (7.01 ± 2.2 mM). Thus, despite a difference in La, there was no difference between · VO2 kinetics during recovery after one sprint and after five sprints. There was a significant difference in · VO2 between the five sprints and 30-s sprint from 70 s to 320 s during recovery, but there were no significant differences in La after 5 min of recovery. There were two phases in · VO2. They consisted of fast oxygen debt and slow oxygen debt. There were also no differences in slow and fast oxygen debts between the two 10-s sprints despite significant differences in blood lactate during recovery. Peak La in the five sprints was not significantly different from that in the 30-s sprint (8.68 ± 1.2 mM). However, slow oxygen debt was significantly greater in the 30-s sprint than in the five sprints. It is concluded that · VO2 kinetics during recovery are not affected by an increase in blood lactate.